Social Spending, Distribution, and Equality of Opportunities : Opportunity Incidence Analysis - Cuesta, Jose (World Bank, Washington, DC, 2013)
Existing evidence forms a body of "conventional wisdom" on the redistributive impact of fiscal policies that has been recently questioned by more disaggregated analyses. This paper proposes an additional extension to the traditional benefit incidence analysis to explore further the extent to which the conventional wisdom holds, as well as to provide effective guidance in fiscal decision making. The benefit incidence analysis extension includes linking fiscal policies with the concept of equality of opportunities. The paper describes this approach and showcases the application of the proposed "opportunity incidence analysis" to six pilot countries: Liberia, Cote d Ivoire, Zambia, Tajikistan, Thailand, and Paraguay. Three main contributions stand out: first, opportunity incidence analysis complements traditional benefit incidence analysis by applying its mechanics to a more forward looking concept of equal opportunity. Second, opportunities can be used to target public spending with higher precision. Third, micro-simulations can be used to understand the cost-effectiveness of alternative spending interventions that seek to improve equality of opportunities. All of these results complement the diagnosis produced by traditional incidence analysis and provide useful information to guide specific policy decisions.